1999
DOI: 10.1074/jbc.274.44.31245
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Mediates Inhibition of Insulin Secretion by Interleukin-1β

Abstract: Interleukin-1␤ (IL-1␤) and prostaglandin E 2 (PGE 2 ), frequently co-participants in inflammatory states, are two well recognized inhibitors of glucose-induced insulin secretion. Previous reports have concluded that the inhibitory effects of these two autacoids on pancreatic ␤ cell function are not related because indomethacin, a potent prostaglandin synthesis inhibitor, does not prevent IL-1␤ effects. However, indomethacin is not a specific cyclooxygenase inhibitor, and its other pharmacologic effects are lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
110
1
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 29 publications
3
110
1
3
Order By: Relevance
“…Increases in islet IL-1␤ during the development of diabetes in an animal model have been reported (7). We reported that specific inhibitors of cyclooxygenase-2 and PGE 2 production prevent IL-1␤ from inhibiting glucose-induced insulin secretion in isolated islets (14). However, the effect of IL-1␤ that inhibits insulin secretion via ROS formation we identified in the current study appears to be independent from PGE 2 production because PGE 2 did not increase ROS levels.…”
Section: Discussioncontrasting
confidence: 54%
See 3 more Smart Citations
“…Increases in islet IL-1␤ during the development of diabetes in an animal model have been reported (7). We reported that specific inhibitors of cyclooxygenase-2 and PGE 2 production prevent IL-1␤ from inhibiting glucose-induced insulin secretion in isolated islets (14). However, the effect of IL-1␤ that inhibits insulin secretion via ROS formation we identified in the current study appears to be independent from PGE 2 production because PGE 2 did not increase ROS levels.…”
Section: Discussioncontrasting
confidence: 54%
“…However, the effect of IL-1␤ that inhibits insulin secretion via ROS formation we identified in the current study appears to be independent from PGE 2 production because PGE 2 did not increase ROS levels. The effect of IL-1␤ that is mediated by PGE 2 to inhibit glucoseinduced insulin secretion may be more potent than the corresponding ROS-mediated effect of IL-1␤ because GCLC overexpression only partially prevented the IL-1␤ inhibitory effect on insulin secretion, whereas treatment with specific cyclooxygenase-2 inhibitors completely prevented IL-1␤-induced inhibition of glucose-induced insulin secretion (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to most mammalian cells, beta cells constitutively and dominantly produce the COX-2 isoform of PGE 2 -generating enzymes rather than COX-1 [5]. Prior studies have demonstrated that PGE 2 inhibits glucose-stimulated insulin secretion (GSIS) in clonal beta cells and isolated islets [6,7], and that selective inhibition of COX-2 attenuates the development of diabetes in the low-dose streptozotocin mouse model and protects rat islets from cytokine-induced inhibition of GSIS [8,9]. Despite the established role of PGE 2 in pancreatic beta cells, the exact molecular mechanisms of PGE 2 -mediated inhibition of insulin secretion remain poorly understood.…”
mentioning
confidence: 99%